2017
DOI: 10.1038/s41598-017-12285-8
|View full text |Cite
|
Sign up to set email alerts
|

Salidroside ameliorates sepsis-induced acute lung injury and mortality via downregulating NF-κB and HMGB1 pathways through the upregulation of SIRT1

Abstract: Sepsis is a life-threatening medical condition. Salidroside, a substance isolated from Rhodiola rosea, possesses antioxidant and anti-inflammatory properties. The effect and mechanism of salidroside on sepsis-induced acute lung injury still remains to be well clarified. Here, we investigated the effect and mechanism of salidroside on septic mouse models and explored the role of salidroside-upregulated SIRT1. Salidroside inhibited the inflammatory responses and HMGB1 productions in bacterial lipopolysaccharide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 43 publications
7
50
0
Order By: Relevance
“…Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs. The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS‐induced ALI and pulmonary contusion . However, our further study indicated that co‐treatment of BMDMs with both Res and LPS prevented the LPS‐induced suppression of SIRT1 (Figure C), demonstrating the important role of Res in activation of SIRT1 signalling.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with the previous report, we observed that Res up‐regulated the expression of SIRT1, whereas LPS moderately reduced the expression of SIRT1 in BMDMs. The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS‐induced ALI and pulmonary contusion . However, our further study indicated that co‐treatment of BMDMs with both Res and LPS prevented the LPS‐induced suppression of SIRT1 (Figure C), demonstrating the important role of Res in activation of SIRT1 signalling.…”
Section: Discussionsupporting
confidence: 93%
“…The results were consistent with previously reports, in which there was lower SIRT1 expression in the inflammatory lungs of animal models with LPS-induced ALI and pulmonary contusion. [26][27][28] However, our further study indicated that co-treatment of BMDMs with both Res and LPS prevented the LPS-induced suppression of SIRT1 ( Figure 7C) In conclusion, this study indicated that Res suppressed lung inflammation of mice with LPS-induced ALI, in association with significantly reduced neutrophil infiltration and production of F I G U R E 8 Schematic diagram of resveratrol (Res)-mediated suppression of ALI through STAT3/SOCS3 signalling. LPS induces oxidative stress and activates STAT3, subsequently induces IL-6, IL-1beta and CXCL15 expression, ultimately causes ALI/ARDS.…”
Section: Res Suppressed M1 Cell-biased Polarization Of Bmdms From Wmentioning
confidence: 63%
“…Furthermore, it was reported that the NF‐κB inhibitor can suppress IL‐1β‐induced production of MMP‐3 and MMP‐13 in human chondrocytes . Recently, 1 study showed that salidroside ameliorated sepsis‐induced acute lung injury and mortality by downregulating the NF‐κB pathway . The current study demonstrated that pretreatment with salidroside prevented NF‐κB p65 phosphorylation and IκBα degradation induced by IL‐1β in human OA chondrocytes.…”
Section: Discussionsupporting
confidence: 52%
“…HMGB1 has attracted increasing attention in recent years as a late inflammatory mediator in the pathophysiology of patients with sepsis . A previous study (Lan et al 2017) indicated that HMGB1 is released 16-24 h after sepsis onset. The late release time and extended duration of HMGB1 provides an abundant time window for clinical treatment, and is thus likely to become a new target for sepsis treatment.…”
Section: Discussionmentioning
confidence: 91%